The Effect of Suppleness And Agility on The Side Kick Ability of Pencak Silat Athletes - Hafid, Fathurrahman; Firdaus (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to analyze the direct and indirect effects between simultaneous flexibility on the ability of side kicks through agility in Pencak Silat athletes. The method used in this study is a quantitative method using the Path Analysis approach. The sample of this study is 25 West Sumatra pencak silat athletes. This study uses a data analysis technique with a Path Analysis approach. Based on the findings and discussions, it can be concluded that: 1) There is a significant direct influence of flexibility on the side kick ability of pencak silat athletes, 2) There is a direct and significant influence of agility on the side kick ability of pencak silat athletes, 3) There is an indirect influence of flexibility on the side kick ability through the agility of pencak silat athletes and 4) There is a significant influence between flexibility and agility simultaneously to the side kick ability of pencak silat athletes.